Decision-making on injury prevention and rehabilitation in professional football: A coach, medical staff, and player perspective - Noesgaard, M. R.; Sæther, S. A. (The Sport Journal, 2023)
Purpose The aim of this study is to research how the decision-making on RTP from the medical staff impact on the perceived short- and long-term performance of the player and the team, from a coach, medical staff, and player perspective.